2018
DOI: 10.1002/dmrr.3001
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid to creatinine ratio correlates with β‐cell function in type 2 diabetes

Abstract: SUA to creatinine ratio correlates with β-cell function in T2DM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…SUA level will increase due to its impaired clearance in individuals with impaired renal function (27).However, many studies ignored the effect of kidney on SUA, while SUA/Cr is a renal function-normalized index and may be a more precise indicator than SUA. A Chinese study based on 713 diabetics revealed that SUA/Cr was significantly associated with b-cell function (11). Another study suggested that SUA/Cr in T2DM patients was closely linked to metabolic syndrome and its components (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SUA level will increase due to its impaired clearance in individuals with impaired renal function (27).However, many studies ignored the effect of kidney on SUA, while SUA/Cr is a renal function-normalized index and may be a more precise indicator than SUA. A Chinese study based on 713 diabetics revealed that SUA/Cr was significantly associated with b-cell function (11). Another study suggested that SUA/Cr in T2DM patients was closely linked to metabolic syndrome and its components (10).…”
Section: Discussionmentioning
confidence: 99%
“…SUA to creatinine ratio (SUA/Cr) is an index of renal function-normalized SUA, reflecting endogenous UA levels more precisely than SUA. Moreover, SUA/Cr is associated with b-cell function, metabolic syndrome and incident chronic kidney disease (10)(11)(12).However, there has been no study focused on the association between SUA/Cr and NAFLD yet.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolites associated only with T2D are involved in kidney function or chronic kidney disease. These include 1,5-anhydroglucitol, creatinine and guanidinoacetate (creatine metabolism) [19],…”
Section: T2d Metabolites and Link To Oxidative Stressmentioning
confidence: 99%
“…Currently, the relationship between SUA and insulin resistance and beta-cell function has been established in several studies in patients with diabetes. [15][16][17][18] However, a large-scale study investigating this relationship in nondiabetic population is still lacking. In the present study, we explored the association of SUA with glucose homeostasis in nondiabetic individuals as assessed by HOMA models, which may help to define the role of SUA in the early natural history of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%